Implementation of The Thematic Village Program In The Empowerment of Small and Medium Enterprises (SMES) In Neglasari District Of Tangerang City - Vera Ulanuari; Riswanda; Leo Agustino (International Journal of Social Sciences Review, 2021)
The focus of this research is the implementation of the Thematic Village Program in Empowerment Small and Medium Enterprises in Neglasari District, Tangerang City. In its implementation there are several problems such as product marketing has not been optimal for banana hump chips SMEs in Kampung Taubat because they are only known by the people of Tangerang City; lack of clarity on capital funding for SMEs in the thematic village Kampung Anggursari dan Kampung Taubat because the use the capital for a business independently and funding so far only focused on the thematic village infrastructure; the lack of development for packaging products for wine in Kampung Anggursari seed needed by businesses; lack of community participation to be active in developing the thematic villages that have been established by the government so that there are only 4 active village or 39 villages in the district thematic Neglasari. The theory used was the implementation theory of Merille S. Grindle consisting of the content of policy and context of policy. The research method that was used was descriptive qualitative aims to provide an overview of data analysis techniques using techniques according to Irawan. The results of this study are the implementation of the thematic village program in empowering SMEs in Neglasari District, Tangerang City has not optimally because there is no budget for thematic village programs from the Tangerang City Government, the distribution and marketing of banana weevil chips in Kampung Taubat is no longer open due to lack of enthusiasts and outlets, lack of development or training from the government for SMEs in Kampung Anggursari due Kampung Anggursari has been declared as an independent village, people who do not participate in thematic village programs. Advice to policy actors in the village thematic programs to provide the program budget thematic villages do actively monitoring the thematic villages, the availability of outlets of SMEs in each district.